Decision Making System Internet Addiction in Children Aged 7-17 Year Use Forward Chaining Method (Case Study : Terik Village – Krian, Sidoarjo) - Elfi Ratna; Ika Ratna (Universitas Muhammadiyah Sidoarjo, 2021)
Based on a survey conducted by the APJII (Indonesian Internet Service Providers Association) team in 2018 with a percentage of more than 64.8% using the internet. The highest percentage is at the age of 7-19 years, which is 91%, this shows that the number of internet users is getting higher every year. This study aims to help treat children who are addicted to the Internet and as advice or a reference for making decisions on how to deal with people who are addicted to the Internet. The method used was to collect data on the distribution of questionnaires or questions that were carried out directly on children aged 7-17 years in the blistering village. The results of external application testing with Likert scale calculations get a percentage result of 78.36% (very useful).